2011
DOI: 10.1007/s11136-011-0003-8
|View full text |Cite
|
Sign up to set email alerts
|

Choice of recall period for patient-reported outcome (PRO) measures: criteria for consideration

Abstract: Shorter recall periods may underestimate symptom burden when symptoms have diurnal or day-to-day fluctuation and may place undue burden on patients. On the other hand, recall intervals that are too long may either over- or underestimate the health state. Therefore, appropriate criteria should be considered given attributes of the disease when selecting an adequate recall period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 20 publications
1
86
0
Order By: Relevance
“…27 The choice of a short recall period may lead to underestimation of symptom severity, when symptoms have a day-to-day fluctuation, or else may place undue burden on the patient, if patients are too ill to frequently complete the questionnaire. However, a long recall period may over- or underestimate the true health status of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…27 The choice of a short recall period may lead to underestimation of symptom severity, when symptoms have a day-to-day fluctuation, or else may place undue burden on the patient, if patients are too ill to frequently complete the questionnaire. However, a long recall period may over- or underestimate the true health status of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, choice of recall period should be affected by the purpose and intended use of the OHIP scores, the patient population, the patients’ disease or condition, the treatment or device, and the study design [38]. Similarly, as noted by Norquist et al “(1) recall depends on what the patient-reported outcome measure captures, its intended use, and attributes of the disease and study; (2) within the same disease area, recall can vary depending on the concept or phenomenon of interest; (3) recall must consider patient burden and their ability to easily and accurately recall the information requested; and (4) recall must be consistent with the duration of the trial and the scheduled clinic visits” [39]. While the choice of the OHIP recall period, such as the one-month or 7-day recall period, may not be substantially different for the patient’s burden, the measured phenomenon (e.g., current perceived oral health versus an average disease impact over a certain time) may be more accurately assessed using a particular recall period.…”
Section: Discussionmentioning
confidence: 99%
“…PRO is defined as any report of the status of a patient’s health condition that comes directly from the patient, without interpretation of the patient’s response by a clinician or anyone else [34]. It highlights the importance of assessing the effectiveness of health care from the patients’ perspective.…”
Section: Methodsmentioning
confidence: 99%